2019
DOI: 10.1016/j.gloplacha.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Indian monsoon variability in response to orbital forcing during the late Pliocene

Abstract: The Asian monsoon is a major component of the global climate system and can be divided into two subsystems, the Indian monsoon and the East Asian monsoon. Insights into monsoon behaviour and dynamics can be gained through studying past warm intervals in Earth's history. One such interval is the Pliocene epoch, specifically the mid-Piacenzian Warm Period (mPWP; 3.264-3.025 Ma). This time is characterised as a period of sustained warmth, with annual mean temperatures 2 to 3°C higher than the pre-industrial era. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 70 publications
4
8
0
Order By: Relevance
“…9 vs. 4f). In fact, this anomalous meridional circulation is closely related to the strengthened Asian summer monsoon (not shown), consistent with previous studies (Zhang et al, 2013;Prescott et al, 2019). In addition, anomalous northerly winds exist in the western tropical Pacific, but southerly winds are located in the central Pacific (Fig.…”
Section: Response In Meridional Circulationsupporting
confidence: 92%
See 1 more Smart Citation
“…9 vs. 4f). In fact, this anomalous meridional circulation is closely related to the strengthened Asian summer monsoon (not shown), consistent with previous studies (Zhang et al, 2013;Prescott et al, 2019). In addition, anomalous northerly winds exist in the western tropical Pacific, but southerly winds are located in the central Pacific (Fig.…”
Section: Response In Meridional Circulationsupporting
confidence: 92%
“…Sarathchandraprasad et al (2017) indicated that the tectonically induced reorganization of the Indonesian throughflow can strengthen the SASM during the mid-Pliocene due to the increased cross-equatorial pressure gradient. Recent study by Prescott et al (2019) highlighted the substantial influence of orbital forcing on the changes in SASM during the mid-Pliocene. The simulations suggest that tectonic uplifts in the South African plateaus can strengthen the SASM as well (Zhang and Liu, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…8 vs 4(f)). In fact, this anomalous meridional circulation is closely related to the strengthened Asian summer monsoon (not shown), consistent with previous studies (Zhang et al, 2013;Prescott et al, 2019). In addition, anomalous northerly winds exist in the western tropical Pacific, but southerly winds are located in the central Pacific.…”
Section: Response In Meridional Circulationsupporting
confidence: 91%
“…These relationships suggest that orbital and greenhouse gas forcings were more influential in strengthening the SoAM during the MPWP than Arctic SIE. This observation is further supported by HadCM3-based study, which indicates that the enhanced SoAM, particularly during MIS KM5c, was driven by elevated CO 2 concentrations (Prescott et al, 2019).…”
Section: Interval III (322-306 Ma Mpwp)supporting
confidence: 70%